Trees in Your Pocket : A Guide to Trees of the Upper Midwest - Rosburg, Thomas (Bur Oak guide., 2012)
"From maples to oaks to birches, Trees in Your Pocket provides identification and natural history information about forty prominent deciduous species found in the Upper Midwest states of Minnesota, Wisconsin, Illinois, Iowa, and Missouri"--P. [16].